2019
DOI: 10.3389/fphys.2019.00267
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril and a Galectin-3 Inhibitor Improve Ischemic Heart Failure in Rabbits by Reducing Gal-3 Expression and Myocardial Fibrosis

Abstract: Objective: Ventricular remodeling is considered the basis of heart failure and is involved in myocardial fibrosis. This study aimed to assess perindopril and a galectin-3 inhibitor (modified citrus pectin, MCP) for their effects on ventricular remodeling and myocardial fibrosis in rabbits with ischemic heart failure. Methods: Rabbits were divided into sham, heart failure (model), MCP, and perindopril groups, respectively. A rabbit model of ischemic heart failure was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“… 25 , 26 Additionally, a Gal-3 inhibitor alleviated collagen deposition and significantly decreased fibrosis. 14 In our study, CTGF and Gla-3 protein levels were suppressed by CCM in rabbits with CHF, which may be a potential mechanism by which CCM attenuated structural remodeling.…”
Section: Discussionsupporting
confidence: 57%
“… 25 , 26 Additionally, a Gal-3 inhibitor alleviated collagen deposition and significantly decreased fibrosis. 14 In our study, CTGF and Gla-3 protein levels were suppressed by CCM in rabbits with CHF, which may be a potential mechanism by which CCM attenuated structural remodeling.…”
Section: Discussionsupporting
confidence: 57%
“…It has been demonstrated that overexpressing CTGF induce cardiac hypertrophy and collagen production and CTGF is a well-characterized downstream mediator of TGF-β1/Smad3 signaling pathway during the fibrotic response [21,22]. Anther study shown the galectin-3 inhibitor alleviated collagen deposition and significantly decreased fibrosis [10]. In our study, the protein level of CTGF, Gla-3 were suppressed with CCM therapy in CHF rabbits.…”
Section: Effect Of Ccm Treatment On Structural Remolding In Heart Faisupporting
confidence: 55%
“…It has been demonstrated that connective tissue growth factor (CTGF) and galectin-3 (Gal-3) are novel pro-fibrotic markers. Those bio-makers are involved in physiological conditions, such as promoting fibroblast proliferation and collagen deposition, thus lead to myocardial structural remolding [9,10]. In addition to alterations in Connexin43 (Cx43) expression, changes in potassium currents are important contributors to myocardial electrical remodeling [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that microvascular dysfunction is one of the major processes in the development of ischemic heart failure [12]. The endothelium of coronary vessels could regulate coronary blood flow in epicardial coronary and intramyocardial microcirculations [13].…”
Section: Discussionmentioning
confidence: 99%